Optimization of Agricultural Land with the Hungarian Algorithm Method (Case Study: Agricultural Land in Tuatuka Village, Kupang Regency) - Adoe, Vera Selviana; Senge, Yitran Detia; Metkono, Marci; Nae, Yohanes (Program Studi Matematika, Universitas Tadulako, 2024)
This research delves into how the Hungarian Algorithm's utilized to streamline workforce allocation, for activities in Tuatuka Village located in Kupang Regency in East Nusa Tenggara region of Indonesia. The primary obstacles encountered include shortage of labor and differences, in skill levels that affect productivity levels significantly. By employing the Hungarian Algorithm a mathematical method is utilized to reduce costs and time associated with assigning tasks effectively by matching workers to duties based on their skills and capabilities. This study includes gathering data by observing and conducting interviews that are later examined using POM QM, for Windows V5 software and manual computations. The results indicate that implementing this method can cut down total project expenses to 35 work hours through task allocation strategies. The adoption of the Hungarian Algorithm has been successful in improving workforce efficiency in agriculture areas leading to output. Decreased resource wastage. Therefore this study aids, in streamlining operations in the industry especially when it comes to managing resources in rural settings.